Pricing Dynamics of Network Utilities in Developing Countries - Chisari, Omar (2012)
This paper examines the pricing of a utility with an underdeveloped network facing a competitive fringe, short-run network adjustment costs, theft of service, and the threat of retaliatory government intervention that is increasing with the price it charges. Under a variety of plausible assumptions (in the context of developing countries) the utility will find its long-run profits enhanced if it exercises pricing restraint in the early stages of network development. These findings provide some useful insights for the design of post-privatization regulatory governance in developing countries where years of price controls have contributed to choking off investment in network expansion.